A külföldi működő tőke szerepe gazdaságunk fejlődésében = Role of foreign working capital in the development of Hungarian economy - Abonyiné Palotás Jolán (2006)
The role of foreign working capital was considerable not only in the initiation of the process of capitalization in Hungary, but it was also an important drive of the economy as long as World War I and even beyond. Although it was less influential during the interval between the two world wars. From 1972 possibilities for foreign capital investments opened up again in the country, but the magnitude of actual investments reached higher proportions only after the collapse of the communist system. On the whole, foreign working capital has always been a key component in the dynamic development of the local Hungarian industries, enhancing rapid technical innovations and modernization. The present paper gives a general outline of its unique role, restricted mainly to the period after the collapse of communism in Hungary.